2006
DOI: 10.1111/j.1460-9568.2006.04886.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol withdrawal induces hyperalgesia mediated by PKCε

Abstract: Symptoms of ethanol withdrawal include heightened responses to sensory stimuli, as well as tremors and convulsions. We tested the hypothesis that repeated episodes of ethanol intake and withdrawal exacerbate the symptoms of alcohol-induced peripheral neuropathy. In contrast to the hyperalgesia produced when an alcohol (6.5%)-containing diet was fed continuously to male rats which took 4 weeks to develop (Dina et al., 2000), feeding alcohol (6.5%) in repeated cycles of 4 days of alcohol followed by 3 days witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 58 publications
10
77
0
Order By: Relevance
“…The mismatch ODN sequence, 5′-GCC AGC G CG ATC TT T CGC CC-3′, corresponds to the PKCε subunit antisense sequence with 2 bases mismatched (indicated in bold typeface). We have previously shown that (at a dose of 40 μg) antisense ODN with this sequence decreases PKCε protein in dorsal root ganglia [19,19,23,52,53,60]. A search of EMBL and NCBI GenBank Rattus norvegicus databases to PKCε identified no homologous sequences.…”
Section: Methodsmentioning
confidence: 99%
“…The mismatch ODN sequence, 5′-GCC AGC G CG ATC TT T CGC CC-3′, corresponds to the PKCε subunit antisense sequence with 2 bases mismatched (indicated in bold typeface). We have previously shown that (at a dose of 40 μg) antisense ODN with this sequence decreases PKCε protein in dorsal root ganglia [19,19,23,52,53,60]. A search of EMBL and NCBI GenBank Rattus norvegicus databases to PKCε identified no homologous sequences.…”
Section: Methodsmentioning
confidence: 99%
“…Pain sensitivity after alcohol administration is associated with altered levels of PKCγ in the cytoplasm of rat motor neurons [71]. In related work, withdrawal-induced hyperalgesia was reversibly inhibited with PKCε oligodeoxynucleotide antisense [72]. Morphine tolerance studies in rats show that PKCγ expression increases substantially after eight days of morphine treatment [73].…”
Section: Pkcγ and Pkcε In Neural Tissuesmentioning
confidence: 99%
“…According to the Substance Abuse and Mental Health Services Administration (SAMHSA), in 2013, about 17 million or 7.2 percent of Americans reportedly had an AUD (SAMHSA, 2013). Chronic alcohol exposure can cause neuronal degeneration in the peripheral and central nervous systems (Egli et al, 2012; Mellion et al, 2011; Obernier et al, 2002) resulting in painful small fiber peripheral neuropathy (Dina et al, 2006; Edwards et al, 2012). The hallmarks of neuropathic pain are allodynia (pain responses to normally innocuous stimuli) and hyperalgesia (a heightened reponses to noxious stimuli).…”
Section: Introductionmentioning
confidence: 99%
“…Protein kinase Cε (PKCε), an intracellular protein kinase, is associated with the alcoholic neuropathy and mechanical hyperalgesia (Dina et al, 2000, 2006; Joseph and Levine, 2010; Shumilla et al, 2005). However, it is difficult to develop truly PKC isoform-selective inhibitors (Roffey et al, 2009).…”
Section: Introductionmentioning
confidence: 99%